(untitled) (Research, Society and Development, 2022)
The face has several pneumatic cavities lined by respiratory epithelium and mucosa, located inside their respective bones and having direct communication with the nasal cavity, these are called sinuses, and the largest of these are the maxillary sinus, which can be affected by a series of malignant neoplasms. This work aims to gather information about malignant neoplasms of the maxillary sinuses, which can serve as an informational source for dental students and professionals in the area. A descriptive narrative literature review was carried out on the proposed theme, using scientific articles available in databases such as BVSalud, PUBMed, Scielo, and Google Scholar as a bibliographic basis. The investigated literature showed that in approximately 80%-90% of cases these neoplasms are squamous cell carcinoma, a malignant epithelial neoplasm that may or may not be keratinized. Malignant neoplasms of the maxillary sinuses are asymptomatic in their early stages, which means that their diagnoses are most often made in an advanced stage. Imaging exams are extremely important for the diagnosis of these neoplasms, especially computed tomography, which makes it possible to perform a precise analysis of the location, extent, and destruction already caused. It is extremely important that dentists become more attentive to the simplest signs and symptoms presented by patients, since, as demonstrated in this work, simple and apparently harmless signs can be indications of the development of malignant neoplasms of the maxillary sinuses.